Evaluating a relationship of factors affecting users’ satisfaction with mobile government services of Abu Dhabi Police - Saif Murshed Almeqbaali, Salem Rashed (2022)
One of the objectives of the Abu Dhabi Police is to improve citizen satisfaction with its services through ICT. The Abu Dhabi Police launched M-government mobile app called “Abu Dhabi Police”. However, despites the issues and concerns about similar M-government services in UAE, there is lack of studies that evaluate the service quality of the M-government police services and how it influence users’ satisfaction. Accordingly, this research evaluated the relationship between service quality, technology and behavioural (personal) profile on users’ satisfaction with M-government police service in Abu Dhabi, UAE. Data were collected from the users of the M-government services of Abu Dhabi Police which are approximately over 950,000 users. However, only 400 questionnaires were distributed and 250 responses were usable for the statistical analysis. Partial Least Squares – Structural Equation Modelling (PLS-SEM) was used to analyse the data. Overall, the research found that about 68 percent (R2 = 0.682) of the variation users’ satisfaction with M-government police services is explained by service quality, technology quality and behavioural (personal) profile. Specifically, the research found that service quality (β = .433, t statistics = 6.477, p < .0001) and technology quality (β = .460, t statistics = 7.248, p < .0001) have significant positive effect with M-government police services. However, the research did not find significant relationship between behavioural (personal) profile and satisfaction with M-government police services (β = .041, t statistics = 0.651, p > .05). The research has contributed to the existing body of knowledge and the practice of providing M-government services to the citizens for their overall satisfaction. The research recommend replicating the study on other M-government services and domains. Further studies should also extend the constructs used in this research and propose a framework for effective M-government service delivery.